Efficiency of steel fibers in shear resistance of reinforced concrete beams without stirrups at different moment-to-shear ratios. (1st June 2019) - Gali, Sahith; Subramaniam, Kolluru V.L.
Highlights: Steel fiber reinforced concrete are tested at a/d ratios of 1.8, 2.25 and 3.0. Using DIC technique, the formation of the critical shear crack which determined shear capacity is identified. The dilatant expansion measured across the critical shear crack depends on the a/d ratio. In beams with higher a/d ratio, there is a larger moment at the shear crack, resulting in larger dilatancy. At the peak load, M/(Vd) at critical shear crack increases with increasing a/d ratio. The increase in the shear capacity due to fibers depends on the M/(Vd) ratio. Abstract: An experimental program is conducted to investigate the effect of the moment-to-shear ratio on the shear capacity of reinforced concrete beams without stirrups. Shear beams made with steel fiber reinforced concrete (SFRC) are tested at shear-span-to-depth (a/d) ratios equal to 1.8, 2.25 and 3.0. Using the digital image correlation (DIC) technique, the critical shear crack is identified. The critical shear crack is formed at the location of the highest moment in the shear span. From measurements across the critical shear crack, a continuous dilatant behavior is observed. There is a continuous increase in the crack opening displacement with progressive slip across the crack faces throughout the load response. The dilatant expansion measured across the critical shear crack depends on the a/d ratio. For a given a/d ratio, the load is sustained for large crack openings in SFRC beams. At a higher a/d ratio, there is a larger applied moment at the shear crack, which produces a larger crack opening with increasing slip displacement across the shear crack. At the peak load, the applied moment (M) to shear (V) ratio given by M/(Vd) at critical shear crack increases with increasing a/d ratio. Larger crack opening with increasing M/(Vd) decreases the efficiency of fibers in providing shear resistance for continued deformation past the peak load.